Noradrenergic Regulation of Cognitive Flexibility: No Effects of Stress, Transcutaneous Vagus Nerve Stimulation, and Atomoxetine on Task-switching in Humans - Tona, Klodiana-Daphne; Revers, Hans; Verkuil, Bart; Nieuwenhuis, Sander (Journal of cognitive neuroscience, 2020)
Cognitive flexibility allows us to adaptively switch between different responsibilities in important domains of our daily life. Previous work has elucidated the neurochemical basis underlying the ability to switch responses to a previously nonreinforced exemplar and to switch between attentional sets. However, the role of neuromodulators in task switching, the ability to rapidly switch between two or more cognitive tasks afforded by the same stimuli, is still poorly understood. We attempted to fill this gap by manipulating norepinephrine levels using stress manipulation (Study 1a, = 48; between-group design), transcutaneous vagus nerve stimulation at two different intensities (Study 1b, = 48; sham-controlled between-group design), and pharmacological manipulation (Study 2, = 24; double-blind crossover design), all of which increased salivary cortisol measures. Participants repeatedly switched between two cognitive tasks (classifying a digit as high/low [Task 1] or as odd/even [Task 2]), depending on the preceding cue. On each trial, a cue indicated the task to be performed. The cue–stimulus interval was varied to manipulate the time to prepare for the switch. Participants showed typical switch costs, which decreased with the time available for preparation. None of the manipulations modulated the size of the switch costs or the preparation effect, as supported by frequentist and Bayesian model comparisons. Task-switching performance reflects a complex mix of cognitive control and bottom–up dynamics of task-set representations. Our findings suggest that norepinephrine does not affect either of these aspects of cognitive flexibility.